2011
DOI: 10.1128/aac.00222-11
|View full text |Cite
|
Sign up to set email alerts
|

Selection, Optimization, and Pharmacokinetic Properties of a Novel, Potent Antiviral Locked Nucleic Acid-Based Antisense Oligomer Targeting Hepatitis C Virus Internal Ribosome Entry Site

Abstract: We have screened 47 locked nucleic acid (LNA) antisense oligonucleotides (ASOs) targeting conserved (>95% homology) sequences in the hepatitis C virus (HCV) genome using the subgenomic HCV replicon assay and generated both antiviral (50% effective concentration [EC 50 ]) and cytotoxic (50% cytotoxic concentration [CC 50 ]) dose-response curves to allow measurement of the selectivity index (SI). This comprehensive approach has identified an LNA ASO with potent antiviral activity (EC 50 ‫؍‬ 4 nM) and low cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…To determine the effect of antagonizing miR-21, primary human macrophages derived from healthy donors were treated with liposomal complexes containing locked nucleic acid (LNA) sequences designed to block miR-21 (LNA antagomiR-21). LNAs are RNA nucleotides containing a modified ribose moiety and were used to antagonize miR functionality here because they are significantly more resistant to enzymatic degradation than RNA [30]. Cells were incubated with autologous serum as an endogenous source of EV-derived miR-21 for 24 h. Relative to nonsense control treatment (LNA-control), inhibition of miR-21 with LNA antagomiR-21 reduced the expression of TLR8 mRNA by 46% ( p < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the effect of antagonizing miR-21, primary human macrophages derived from healthy donors were treated with liposomal complexes containing locked nucleic acid (LNA) sequences designed to block miR-21 (LNA antagomiR-21). LNAs are RNA nucleotides containing a modified ribose moiety and were used to antagonize miR functionality here because they are significantly more resistant to enzymatic degradation than RNA [30]. Cells were incubated with autologous serum as an endogenous source of EV-derived miR-21 for 24 h. Relative to nonsense control treatment (LNA-control), inhibition of miR-21 with LNA antagomiR-21 reduced the expression of TLR8 mRNA by 46% ( p < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these data suggest that chloroquine may be binding to miRs to prevent TLR8 induction within endosomal compartments and that multiple miRs are most likely capable of TLR8 activation in this system. To suppress the effect of miR-21, a miR antagonist was designed with a modified LNA backbone, which enhances resistance to degradation when compared to RNA and has been shown to persist in vivo for over a week [30]. Our future investigations will be directed toward the identification of additional EV-derived miR agonists for TLR8 that are associated with SLE and the therapeutic development of LNA-based antagonists to block miR-induced inflammatory responses in vivo using SLE animal models.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, a single nucleotide modification (e.g., perfect match vs. one base pair mismatch) may lead to major, or ''all or none,'' phenotypic changes. The QM modeling data explains and illustrates reasons underlying some of the unexpected observations relating to major phenotypic changes observed for otherwise ''closely related'' molecules (vide infra) (Seth et al, 2009;Straarup et al, 2010;Laxton et al, 2011;Stanton et al, 2012;Hagedorn et al, 2013).…”
Section: Discussionmentioning
confidence: 78%
“…For instance, it has been reported that small structural modifications of antisense oligonucleotides (e.g., LNAs) have profound effects on these relations, which are observed as property changes. (Seth et al, 2009;Straarup et al, 2010;Laxton et al, 2011;Stanton et al, 2012). The mechanisms behind this ''property diversity'' are not understood, and it is clear that a reductionist viewpoint, where the complex properties of a given oligonucleotide (e.g., tissue and cellular uptake, pharmacokinetics, toxicity) are assigned by a simple correlation with the nucleobase sequence alone, neither describes nor predicts these structure/activity changes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, different synthetic molecules targeting specific RNA motifs essential for viral RNA multiplication have been exploited as therapeutic agents. [46][47][48][49][50][51] Furthermore, the IRES-inhibitory property of IRAB was observed both in in vitro translation assays using cell free lysates and in cells transfected with infectious RNA revealing that the primary targeted event is viral RNA translation, which is IRES-dependent. 7 In agreement with this, a specific decrease of viral protein synthesis occurred in transfected cells concomitantly to a reduction in virus yield in the presence of IRAB (2 mM).…”
Section: Discussionmentioning
confidence: 99%